1983
DOI: 10.1111/j.1476-5381.1983.tb10728.x
|View full text |Cite
|
Sign up to set email alerts
|

The spasmogenic action of potassium chloride in guinea‐pig trachealis

Abstract: Tissue bath experiments showed that potassium chloride (KCl) at 10–40 mmol l−1 evoked spasm of guinea‐pig trachealis which was unaffected by atropine (1 μmol l−1), mepyramine (1 μmol l−1), tetrodotoxin (3 μmol l−1) or indomethacin (2.8 μmol l−1). Spasm evoked by KCl was depressed in Ca2+‐free Krebs solution or by exposure of tissues to LaCl3 (0.25–1 mmol l1). Extracellular electrical; recording showed that the spasm evoked by KCl 10 mmol l−1 was associated with promotion of electrical slow wave activity. Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
3

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 11 publications
5
25
3
Order By: Relevance
“…When the tone loss observed in vehicle-treated control tissues was compared with that seen in verapamil-treated trachea (Table 2) it became evident that verapamil, too, has little effect on trachealis tone. Clearly, the administration of organic calcium antagonists is not equivalent to removal of extracellular Ca2+ since the latter procedure caused almost total tone loss (Table 2) and was less able to discriminate among spasmogens (Foster et al, 1983b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the tone loss observed in vehicle-treated control tissues was compared with that seen in verapamil-treated trachea (Table 2) it became evident that verapamil, too, has little effect on trachealis tone. Clearly, the administration of organic calcium antagonists is not equivalent to removal of extracellular Ca2+ since the latter procedure caused almost total tone loss (Table 2) and was less able to discriminate among spasmogens (Foster et al, 1983b).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments where CaCl2 was used as an agonist required that a depolarizing Ca2'-free PSS be employed. The depolarizing, Ca2+-free PSS of Spedding (1982) contained K+ at 40mmoll-i and this concentration of K+ evokes profound (approximately 40 mV) depolarization of guinea-pig trachealis (Foster et al, 1983b). Accordingly, the depolarizing, Ca2'-free media used in the present study also contained K+ at 40 mmol 1`.…”
Section: Intracellular Electrophysiological Recordingmentioning
confidence: 99%
“…On guineapig isolated trachea, as on the rabbit isolated aorta (Bertaccini et al, 1984), oxmetidine behaved as an antispasmogenic agent, its effect being independent of the type of stimulant employed to contract the preparation. The ability of oxmetidine to antagonize, to approximately the same extent, the stimulatory effect of compounds acting via different mechanisms (KCI exerts a direct action on tracheal smooth muscle and involves both depolarization and influx of Ca2" (Foster et al, 1983), whereas ACh and histamine involve depolarization with little effect on Ca2" influx (Ahmed et al, 1984) suggests that it may have a complex action, interfering with the transport at the membrane level and with the release or utilization of calcium ions at intracellular sites. Indeed, in the rabbit aorta oxmetidine behaved similarly to nitroglycerin, a compound which is assumed to act predominantly on intracellular calcium (Ito et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…(19). Although we did not investigate the effect of diabetes on the binding characteristics of muscarinic receptors in rat trachea, the increased contractilities to ACh and KC1 in diabetic tracheas without any change in the sensitivity (pD 2 ) indicate that the hyper-responsiveness may be dependent to the alterations in (22,23,24). It has been shown that oxidative stress is responsible for the increased contractile responsiveness of diabetic vasculature by increasing diacylglycerol -protein kinase C (DAC-PKC) activity which stimulates IP 3 induced Ca +2 release from intracellular organelles leading to intracellular Ca +2 accumulation in diabetes mellitus (25,26).…”
Section: Discussionmentioning
confidence: 99%